2023
DOI: 10.9734/jamps/2023/v25i6622
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Delivery in Nigeria: Traditional Medicine Practitioners Perspectives to Universal Health Coverage and Traditional Medicine Integration with Conventional Medicine

Abstract: Introduction: The knowledge, attitude, and practice of Traditional Medicine Practitioners (TMPs) are key to achieving effective and sustainable integration of all forms of Traditional, Complementary and Alternative Medicine (TCAM) and health services towards Universal Health Coverage (UHC). In this study, the operational and psychological readiness of Traditional Medicine Practitioners towards integration with the conventional health system was examined by critically considering the various factors central to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Studies have shown that a considerable portion of the population in developing countries, such as African nations, rely on traditional medicine for primary healthcare, with usage rates reaching up to 80%. 4 , 5 , 6 However, it is important to note that the use of CAM is not exclusive to developing countries, as research has also highlighted its prevalence among individuals in developed countries. 7 , 8 Factors contributing to the increased use of CAM in developing countries include its accessibility, affordability, and concerns regarding the adverse effects of chemical drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a considerable portion of the population in developing countries, such as African nations, rely on traditional medicine for primary healthcare, with usage rates reaching up to 80%. 4 , 5 , 6 However, it is important to note that the use of CAM is not exclusive to developing countries, as research has also highlighted its prevalence among individuals in developed countries. 7 , 8 Factors contributing to the increased use of CAM in developing countries include its accessibility, affordability, and concerns regarding the adverse effects of chemical drugs.…”
Section: Introductionmentioning
confidence: 99%